Interactive flipbook e-module for salon management learning: A digital innovation in beauty education - Nurina Ayuningtyas; Lilis Jubaedah; Ria Maharani (Jurnal Pendidikan Teknologi Kejuruan, 2025)
The limited availability of adequate learning media in beauty services business management education has resulted in decreased student engagement and reduced entrepreneurial interest in vocational beauty programs. This study developed and validated an innovative flipbook-based e-module that uniquely integrates theoretical business management principles with industry-specific practical applications for beauty services operations. The research employed a Research and Development (R&D) methodology using the systematic ADDIE model across five phases: analysis, design, development, implementation, and evaluation. Unlike conventional static digital materials, the developed e-module featured interactive 18-page content with multimedia integration, page-turning animations, embedded assessment tools, and comprehensive coverage of business planning, financial management, human resource management, marketing strategies, and risk management specifically contextualized for beauty services business operations. Expert validation demonstrated substantial improvement through iterative development, with material expert scores increasing from 73.3% to 93.3% and media expert scores from 85.0% to 90.0%, achieving an overall expert validation of 91.7%. Student practicality testing revealed 86.5% effectiveness, with notably higher performance in collaborative learning contexts (93.0%) compared to individual assessment (80.0%), empirically supporting social learning effectiveness in vocational education. The validated e-module successfully addressed critical gaps in specialized digital resources for vocational beauty education by combining theoretical knowledge with practical industry applications through an innovative flipbook format. This research contributes novel insights into interactive multimedia applications in vocational contexts and provides a replicable framework for developing industry-specific educational resources. The study's practical implications include enhanced student engagement in salon management education and improved preparation for beauty industry entrepreneurship, offering significant potential for widespread implementation in beauty education programs globally.